Status of Human-Wildlife Conflict and Mitigation Measures Adopted by Locals in Shivapuri Nagarjun National Park, Kathmandu Nepal (Nepal Journal of Environmental Science, 2024)
Human Wildlife Conflict (HWC) is one of the major challenges for wildlife conservation globally. This study assessed the status of HWC and the associated mitigation measures in two villages - Okhreni and Chilaune - of Sundarijal Shivapuri Buffer Zone User Committee at Shivapuri Nagarjun National Park (SNNP). Primary data were collected through household questionnaire surveys; key informant interviews and secondary data were collected from official records of SNNP, relevant journals, books, and reports. The survey was conducted in 115 HHs of both villages. 90 HHs were surveyed out of 300 HHs in Okhreni whereas 25 HHs were surveyed out of 50 HHs in Chilaune. Likert scale was used to identify the most problematic animal species involved in HWC. Wild boar (Sus scrofa), Himalayan Black Bear (Ursus thibetanus), crested porcupine (Hystrix brachyuran), rhesus monkey (Macaca mulatta) and barking deer (Muntiacus muntijak) are the major animal species involved in HWC. 95% respondents from Okhreni and 97% respondents from Chilaune experienced crop damage by wild animals, with those near the forest being more affected. Maize was the most targeted crop followed by millet and wheat. Only a single case of human injury has been registered in the last five years. Crop depredation by wild boar was most prevalent in the study area. People from both villages are not satisfied with the existing compensation measures. However, the lack of incidences of livestock depredation and human injuries and fatalities combined with peoples’ awareness about the significance of wildlife could be the probable reasons for positive attitudes towards wildlife and wildlife conservation in SNNP. People should be encouraged to cultivate less preferable and unpalatable crops and plants that are economically profitable as well. This could provide an alternative source of income and help reduce the incidences of HWC in the study area.